Safety of measles-containing vaccines in post-marketing surveillance in Anhui, China - Meng, Fan-Ya (PLoS One, 2017)
The safety of measles vaccination is of great interest and importance to public health practice and the general society. We have analyzed the adverse events following immunization (AEFIs) of currently used measles-containing vaccines (including live attenuated measles vaccine, live attenuated measles and rubella combined vaccine, live attenuated measles and mumps combined vaccine, live attenuated Measles, Mumps and Rubella Combined Vaccine) in Anhui Province, China. From 2009 to 2014, 9.9 million doses of measles-containing vaccines were administrated and 1893 AEFIs were found (191.4 per million doses), of which, 33 serious AEFIs (3.3 per million vaccine doses) were reported. 59.4% (1124 cases) were male cases, and 85.1% (1611 cases) occurred in persons aged < 1 year. 93.3% (1766 cases) occurred at the first dose of vaccination and 95.9% (1815 cases) were found within 3 days after vaccination. This study presents up-to-date data and suggests that the measles-containing vaccines used in Anhui Province of China are safe.